Interaksi Pancasila, Teknologi, dan Pendidikan: Analisis Kritis atas Tantangan Globalisasi Digital di Indonesia : Interaction of Pancasila, Technology and Education: Critical Analysis of the Challenges of Digital Globalization in Indonesia - Nayma Asfi Keisya; Nazua Meutia Hasanah; Qothrun Nada Nurul Janah; Aisyah Mandari Ramadhani; Lisna Amelia Putri; Ika Nur'aini Maisyaroh (Litera Academica Publishing, 2025)
Digital globalization has brought significant transformations in education while simultaneously posing serious challenges to the sustainability of Pancasila values as the foundation of national life. This article aims to critically analyze the interaction between Pancasila, technology, and education in addressing the dynamics of digital globalization in Indonesia. The study employs a qualitative literature review method, using normative–philosophical analysis and critical examination of educational policies and digital technology practices. The findings reveal that although digital technology expands access to education and enhances learning effectiveness, it also carries the risks of value erosion, rising individualism, and cultural penetration that may weaken Pancasila-based character. The critical analysis emphasizes the urgency of integrating Pancasila values into digital curricula, promoting technology literacy grounded in Pancasila ethics, and strengthening the role of educators in cultivating national identity in the global era. The study concludes that a synergistic interaction among Pancasila, technology, and education is essential to safeguarding national values while harnessing the opportunities of digital globalization for Indonesia’s progress.